PENGARUH LAMA WAKTU PEMERAMAN DENGAN PENAMBAHAN PERASAN JERUK NIPIS (Citrus aurantiifolia) TERHADAP AROMA DAN RASA TELUR ASIN - Tegar Solehchatas; Doso Sarwanto; Sulistyaningtyas; Citopartusi Tjahyani (MEDIA PETERNAKAN, 2023)
The research entitled "The Effect of Baking Time With the Addition of Lime Juice (Citrus aurantiifolia) on the Aroma and Taste of Salted Eggs" was carried out from March 5 to March 20, 2023. This research aims to determine the effect of the length of salting time with the addition of lime juice (Citrus aurantiifolia) on the scent and taste of salted eggs. The research material used was 60 duck eggs, lime and salt. This research used an experimental method with a completely randomized design (CRD) consisting of four treatments, namely P1 (6 days salting), P2 (9 days salting), P3 (12 days salting), and P4 (15 days salting). Each treatment consisted of 30 panelists as replicates. Parameters measured were the scent and taste of salted eggs which were produced using 30 untrained panelists. The results of the analysis of variance showed that the different salting times with the addition of 5 ml of lime juice (Citrus aurantiifolia) had no significant effect (P<0.05) on the scent of salted eggs which produced a fishy scent close to slightly fishy. The different duration of ripening with the addition of 5 ml of lime juice (Citrus aurantiifolia) had a very significant effect (P<0.05) on the taste of salted egg which produced a good taste. Keywords: Salting time, lime juice, salted egg